1996
DOI: 10.1128/jcm.34.6.1380-1385.1996
|View full text |Cite
|
Sign up to set email alerts
|

Genetic identification of cryptic genospecies of Haemophilus causing urogenital and neonatal infections by PCR using specific primers targeting genes coding for 16S rRNA

Abstract: Previous genetic analysis of Haemophilus influenzae strains isolated from genital and neonatal infections identified a group of biotype IV that constitutes a cryptic genospecies only distantly related to H. influenzae and H. haemolyticus. Small-subunit rRNA genes of two representative strains of this genital Haemophilus genospecies (strains 16N and 2406) were sequenced. The analysis indicated that these strains form a monophyletic unit with H. haemolyticus and H. influenzae biogroups Influenzae and Aegyptius a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Previous phylogenetic analysis of the sequenced 16S rRNA gene suggested that H. quentini was more closely related to H. haemolyticus than H. influenzae Quentin et al (1996). However, this was not fully determined beyond the initial 16S rRNA comparison.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous phylogenetic analysis of the sequenced 16S rRNA gene suggested that H. quentini was more closely related to H. haemolyticus than H. influenzae Quentin et al (1996). However, this was not fully determined beyond the initial 16S rRNA comparison.…”
Section: Resultsmentioning
confidence: 96%
“…Initially DNA-DNA hybridisation and restriction fragment length polymorphism identified that at least a subset of H. influenzae biotype IV may actually be distinct, but still related, albeit distantly, from both H. influenzae and Haemophilus haemolyticus Quentin et al (1993).Subsequent phylogenetic analysis of a partial sequence of the 16S rRNA gene of two strains of H. influenzae biotype IV found that a proportion of H. influenzae biotype IV were actually more closely related to H. haemolyticus than H. influenzae Quentin et al (1996) and unofficially renamed 'Haemophilus quentini', described as a "cryptic genospecies" since it cannot be distinguished phenotypically from H. influenzae Quentin et al (1996). Since this discovery, it has been identified as the cause of urinary tract infections in men Glover et al (2011) and neonatal bacteraemia through 16S rRNA sequencing Giufre et al (2015); Hubbard et al (2016); Mak et al (2005).…”
Section: Introductionmentioning
confidence: 99%
“…Haemophilus strains isolated from neonatal and genital tract infections (4). Members of this species comprise part of the bacterial population identified as H. influenzae biotype IV in biochemical tests and were previously referred to as "a cryptic genospecies of Haemophilus" (2,11,12). They form a homogenous group with unique multilocus enzyme electrophoresis patterns, outer membrane protein profiles, and fimbrial protein gene sequences (2,9).…”
Section: H Quentini Is a New Species Recently Proposed For A Group Ofmentioning
confidence: 99%
“…They form a homogenous group with unique multilocus enzyme electrophoresis patterns, outer membrane protein profiles, and fimbrial protein gene sequences (2,9). In 16S rRNA sequence analysis, they form a monophyletic unit with a closer relation to Haemophilus haemolyticus than to H. influenzae (12).…”
Section: H Quentini Is a New Species Recently Proposed For A Group Ofmentioning
confidence: 99%
“…Eight biotypes exist for each species, designated biotype I through biotype VIII (3-6). Despite having limited discriminatory power, when used in conjunction with other methods including newer genetic tools, biotyping may be helpful in the clinical laboratory to identify Haemophilus aegyptius (biotype III), which causes bacterial conjunctivitis 7, and Haemophilus quentini (biotype IV), which causes urogenital and neonatal infections (8).…”
Section: Biotyping Of Haemophilus Influenzae and Haemophilus Parainflmentioning
confidence: 99%